Linking the Critical Chain Project Management literature - Luiz, Octaviano Rojas [UNESP]; Souza, Fernando Bernardi de [UNESP]; Rojas Luiz, Joao Victor [UNESP]; Jugend, Daniel [UNESP] (Emerald Group Publishing Ltd, 2019)
Purpose The purpose of this paper is to analyze the state of the art in Critical Chain Project Management (CCPM), outlining the CCPM literature to date, in an effort to guide future studies. Design/methodology/approach The paper is based on a bibliometric analysis using Scopus and Web of Science databases. The authors identified the principal journals, articles and authors regarding the research theme, as well as the authors elaborated co-citation and co-occurrence network maps to support the analysis. Findings The authors described five co-citation clusters: Fundamentals of Critical Chain, Scheduling, Operations Research, Multi-project and Network, and General Project Management. The most frequently occurring keywords were: project management, critical chain, scheduling and theory of constraints. Observing the distribution, the expression project management occupied a central position, connecting two other clusters, represented by the keywords scheduling and critical chain. The authors proposed an evolutive framework for the CCPM state of the art in three stages, according to the most frequent topics identified: Conceptual, Deepening of Applications and Methodological Maturity. Originality/value This research adopts a systematic approach based on bibliometric tools, which allows a more rigorous organization of the literature. Co-citation and keyword co-occurrence maps provide evidence of how the main themes in CCPM relate. Besides, the presented historical framework allows new research in CCPM to be directed to the most recent topics of interest that have gaps to be explored.
Keywords: Systematic literature review; Network analysis; Critical Chain Project Management (CCPM); Time management